Trade, gravity and sudden stops: On how commercial trade can increase the stability of capital flows - Eduardo A. Cavallo (Inter-American Development Bank, Research Department, 2006)
Financial stability is an important policy objective, since crises are associated with large economic, social and political costs. Promoting stability requires preventing 'sudden stops' in capital flows, which are events in which foreign financing abruptly disappears. This paper contributes to the discussion by providing new theoretical and empirical evidence on the causal connection between lack of exposure to commercial trade and proclivity to sudden stops. On the theoretical front, the paper shows how exposure to trade raises the creditworthiness of countries and reduces the probability of sudden stops. In relatively closed economies, sudden stops (when they occur) are more harmful and thus the option to default on the inherited debt is more attractive. Therefore, conditional on the amount that lenders are willing to loan, decreased exposure to trade increases the likelihood of default. A sudden stop takes place when the borrowers reject the amount that lenders want to loan: they receive no new funding and they concurrently default on the outstanding debt to 'ease the pain'. This proposition is tested using 'gravity estimates', which are based on countries' geographic characteristics, as appropriate instruments for trade. The results indicate that, all else equal, a 10 percentage point decrease in the trade to GDP ratio increases the probability of a sudden stop between 30 percent and 40 percent. The policy implications are unambiguous: increasing the tradable component of a country's GDP will, ceteris paribus, reduce the vulnerability of that country to sudden stops in capital flows.
Keywords: F32; F36; F41; 330; Sudden Stops; Current Account Adjustment; Trade; Gravity Model; Kapitalmobilität; Kapitalimport; Leistungsbilanz; Außenwirtschaft; Gravitationsmodell; Theorie; Welt